A Rare Incidental Finding of a Foreign Body in the Nasopharynx during Adenotonsillectomy - Waleed M. Alshehri; Bandar Al-Qahtani (Case Reports in Otolaryngology)
Diverse foreign bodies may become lodged in the aerodigestive tract, and the discovery of such foreign bodies is an expected scenario for health-care practitioners. The foreign body insertion may be accidental or deliberate, and the object may be organic or inorganic. Most accidental foreign body aspirations occur in children, and some such cases are potential threats that go unnoticed. Very few cases of foreign bodies in the nasopharynx have been reported. Herein, we describe an unusual case in which a foreign body in a child’s nasopharynx went unnoticed for 1 year and was detected intraoperatively.